Adapting clinical pharmacy staffing models during the COVID‐19 pandemic: Lessons learned and considerations for future disaster planning. Issue 1 (15th December 2020) - Thompson Bastin, Melissa L.; Berger, Karen; Adams, Christopher D.; Altshuler, Jerry; Dixit, Deepali; Effendi, Muhammad K.; Johnston, Jackie P.; Lemieux, Diana G.; Lemieux, Steven M.; Littlefield, Audrey J.; Owusu, Kent A.; Rose, Christina; et al.
Abstract: Introduction: In response to the coronavirus disease 2019 (COVID‐19) pandemic, health care institutions have faced challenges necessitating operational agility to facilitate provision of optimal patient care. This research was performed to elucidate how pharmacy departments adapted their staffing models, and the impact on frontline staff satisfaction. Methods: Critical care pharmacists in the American College of Clinical Pharmacy (ACCP) and the American Society of Health‐System Pharmacists list‐serves were electronically invited to participate in a 28‐question survey between April and May 2020. Likert‐like questions used a 1 to 5 (strongly agree to strongly disagree) scale, and responses were compared based on the degree of satisfaction with implemented pharmacy leadership strategies. Practice model changes were compared before and during the COVID‐19 pandemic. Multivariate logistic regression was used to assess the effects of independent variables on the primary outcome ‐ satisfaction with pharmacy leadership response. Results: Respondents (N = 168) representing 40 states in the United States participated. Forty percent of respondents experienced a surge, 68% experienced a staffing model change, and 65% were satisfied overall with their pharmacy leadership's response to the COVID‐19 pandemic. Both specialists (50% vs 21%, P = .013) and unit‐based generalists (65% vs 35%, P  < .001) rounded less frequently in response to the COVID‐19 pandemic. Disagreement with "Satisfied with leadership efforts to protect staff (limiting in‐person meetings, changing code response)" decreased the odds of satisfaction by 96% (odds ratio [OR] 0.043 [95% confidence interval (CI) 0.005‐0.336], P = .003). Disagreement with "Satisfied with voice of front‐line staff" was associated with an 84% reduction in satisfaction (OR 0.165 [95% CI 0.049‐0.549], P = .003). Eliminating in‐person rounds was associated with a 95% decrease in satisfaction with pharmacy leadership (OR 0.053 [95% CI 0.007‐0.392], P = .004). Disagreement with "I believe I am at increased risk for COVID‐19 due to departmental staffing decisions" increased satisfaction (OR 3.8, 95% CI [1.06‐13.91], P = .041). Conclusion: Frontline staff perceptions can inform practice model changes to improve employee satisfaction while providing safe, reliable, and responsible patient care.